Long‐Term Geomagnetically Induced Current Observations From New Zealand: Peak Current Estimates for Extreme Geomagnetic Storms. Issue 11 (4th November 2017) - Rodger, Craig J.; Mac Manus, Daniel H.; Dalzell, Michael; Thomson, Alan W. P.; Clarke, Ellen; Petersen, Tanja; Clilverd, Mark A.; Divett, Tim
Abstract: Geomagnetically induced current (GIC) observations made in New Zealand over 14 years show induction effects associated with a rapidly varying horizontal magnetic field (d BH /d t ) during geomagnetic storms. This study analyzes the GIC observations in order to estimate the impact of extreme storms as a hazard to the power system in New Zealand. Analysis is undertaken of GIC in transformer number six in Islington, Christchurch (ISL M6), which had the highest observed currents during the 6 November 2001 storm. Using previously published values of 3, 000 nT/min as a representation of an extreme storm with 100 year return period, induced currents of ~455 A were estimated for Islington (with the 95% confidence interval range being ~155–605 A). For 200 year return periods using 5, 000 nT/min, current estimates reach ~755 A (confidence interval range 155–910 A). GIC measurements from the much shorter data set collected at transformer number 4 in Halfway Bush, Dunedin, (HWB T4), found induced currents to be consistently a factor of 3 higher than at Islington, suggesting equivalent extreme storm effects of ~460–1, 815 A (100 year return) and ~460–2, 720 A (200 year return). An estimate was undertaken of likely failure levels for single‐phase transformers, such as HWB T4 when it failed during the 6 November 2001 geomagnetic storm, identifying that induced currents of ~100 A can put such transformer types at risk of damage. Detailed modeling of the New Zealand power system is therefore required to put this regional analysis into a global context. Key Points: Analysis of a 14 year data set of GIC in a transformer in Islington, New Zealand, shows peaks correlated with local H ′ Peak GIC values are very poorly correlated with global geomagnetic indices ( ap, Kp, and aa *), and weakly correlated with local ak index values Estimated peak GIC at Islington for a 100 year return period geomagnetic storm is ~155–605 A, and ~155–910 A for 200 years